2013
DOI: 10.1007/jhep11(2013)072
|View full text |Cite
|
Sign up to set email alerts
|

The M5-brane action revisited

Abstract: We construct an alternative form of the M5-brane action in which the six-dimensional worldvolume is subject to a covariant split into 3+3 directions by a triplet of auxiliary fields. We consider the relation of this action to the original form of the M5-brane action and to a Nambu-Poisson 5-brane action based on the Bagger-Lambert-Gustavsson model with the gauge symmetry of volume preserving diffeomorphisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 85 publications
0
42
0
1
Order By: Relevance
“…Various formulations of the action for an M5-brane exist, which impose the self-duality constraint in different ways [34][35][36][37][38][39]. The different formulations are believed to be equivalent, at least classically [39,40]. We will use the approach of Pasti, Sorokin and Tonin (PST) [34][35][36], which we find to be the simplest for our purposes.…”
Section: )mentioning
confidence: 99%
“…Various formulations of the action for an M5-brane exist, which impose the self-duality constraint in different ways [34][35][36][37][38][39]. The different formulations are believed to be equivalent, at least classically [39,40]. We will use the approach of Pasti, Sorokin and Tonin (PST) [34][35][36], which we find to be the simplest for our purposes.…”
Section: )mentioning
confidence: 99%
“…So far in the literature, there are three alternative descriptions of the complete M5brane actions: (i) the original M5-brane action [7,8]. (ii) the M5-brane action in the 3+3 formulation [17,18], and (iii) the M5-brane action in the dual formulation constructed in [16] and this paper. Although the off-shell actions from different descriptions are different from one another, it was shown that they all agree on-shell.…”
Section: Gauge-fixing Auxiliary Fieldsmentioning
confidence: 99%
“…The projector matrix P ⊥ was called Π in[17] and[18]. The choice made in this paper is purely because of typesetting.…”
mentioning
confidence: 99%
“…More recently it is shown by construction in [10] that, also within the Green-Schwarz approach, there exists an alternative formulation of a single supersymmetric M5-brane. In this formulation, there are three auxiliary scalar fields.…”
Section: The M5-brane Actionsmentioning
confidence: 99%